Popular Culture Embodying Modernity-Treatment of Popular Culture in Kolatkar’s "Chirimiri" - Aher, Jayashri Balasaheb (Advances in Social Sciences Research Journal, 2019)
Abatract: The article investigates the treatment of popular culture in a slender collection of poems in Marathi by Arun Kolatkar titled ‘Chirimiri’ (meaning a small amount given in bribe) which was published in 2003, by Ashok Shahane’s Prass Publication, Mumbai. Arun Kolatkar , an important bilingual poet composed poetry in Marathi and in English. Most his post 1970s poems in both the languages are an important document of contemporary social, cultural and literary happenings. In his own idiosyncratic, objective and ironic fashion, Kolatkar depicts with maximum subtlety, the people, places, events and happenings in the metropolis of Mumbai. This article is a modest attempt to see the reflection of popular culture with all its popular and political aspects. The basic argument of the article is that any civilization in its embodiment of modernity brings total metamorphosis in the forms of popular culture. Many times altogether new forms of popular culture emerged with advancement of technology and its socio-cultural impact on that society. A very few old forms of popular culture survive but they adopt many changes in all its aspects including the psychology of the audience. The book ‘Chirimiri’ records the contemporary state and status of the most powerful cultural and religious movement, the ‘bhakti’ movement of the ‘warkari’ sect in Hinduism. The forces of urbanization, industrialization and globalization have corrupted the ways and means of this important non-brahminic movement only besides ‘Mahanubhav Movement’ by Chakradhar. Despite its spiritual deterioration the ‘wari’ (pilgrimage to Pandharpur on foot) can still be viewed as an as an important religious-cultural phenomenon with maximum public participation. But embodying modernity of urban pilgrims has changed their attitude towards this pilgrimage.